=1/2.(2/1.3 + 2/3.5 + 2/5.7 +.....+ 2/49.51)
=1/2.(1-1/3+1/3-1/5+1/5-1/7+.....+1/49-1/51)
=1/2.(1-1/51)
=1/2.50/51
=25/51
=1/2.(2/1.3 + 2/3.5 + 2/5.7 +.....+ 2/49.51)
=1/2.(1-1/3+1/3-1/5+1/5-1/7+.....+1/49-1/51)
=1/2.(1-1/51)
=1/2.50/51
=25/51
\(\frac{1}{1.3}+\frac{1}{3.5}+\frac{1}{5.7}+...+\frac{1}{49.51}\)
\(=\frac{1}{2}.\left(\frac{2}{1.3}+\frac{2}{3.5}+\frac{2}{5.7}+...+\frac{2}{49.51}\right)\)
\(=\frac{1}{2.}\left(1-\frac{1}{1}+\frac{1}{3}-\frac{1}{3}+\frac{1}{5}-\frac{1}{7}+...+\frac{1}{49}-\frac{1}{51}\right)\)
\(=\frac{1}{2}.\left(1-\frac{1}{51}\right)\)
\(=\frac{1}{2}.\frac{50}{51}\)
\(=\frac{25}{51}\)
Đặt biểu thức trên là A, ta có:
\(A=\frac{1}{1.3}+\frac{1}{3.5}+\frac{1}{5.7}+...+\frac{1}{49.51}\)
\(\Rightarrow2A=\frac{2}{1.3}+\frac{2}{3.5}+\frac{2}{5.7}+...+\frac{2}{49.51}\)
\(\Rightarrow2A=1-\frac{1}{3}+\frac{1}{3}-\frac{1}{5}+\frac{1}{5}-\frac{1}{7}+...+\frac{1}{49}-\frac{1}{51}\)
\(\Rightarrow2A=1-\frac{1}{51}\)
\(\Rightarrow2A=\frac{50}{51}\)
\(\Rightarrow A=\frac{25}{51}\)